September 2020 Placement Ads (The Accounting Review, 2020)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on ‘‘Career Center,'' or call our office at 941-921-7747.FUDAN UNIVERSITY, School of Management, Accounting Department invites applications for multiple positions in accounting for appointments beginning September 1, 2021. The ranks of Assistant Professor, Associate Professor, and Full Professor are open. We offer competitive salary, research fund, and housing allowance commensurate with qualifications and experience. Interested candidates are to submit their electronic application package, with the subject heading “Fudan Accounting Faculty Application 2020, to: hrfdms@fudan.edu.cn. The required application materials are cover letter, curriculum vitae, and samples of published or working papers. Relevant evidence of teaching effectiveness will be a plus if available. Three letters of recommendation can be sent later in separate emails directly to: hrfdms@fudan.edu.cn. Contact Information: Ms. Yan Zhou, Faculty Development Office, School of Management, 670 Guo Shun Road, Phone: 86-21-25011470; Email: hrfdms@fudan.edu.cn; Website: https://www.fdsm.fudan.edu.cn/En/Faculty_Recruiting.aspxTENNESSEE TECH UNIVERSITY, Business Office has a position open for an Accountant 3. Complete position summary and application procedure available at: https://jobs.tntech.edu/ Application deadline is July 13th, 2020. Tennessee Tech University is an AA/EEO employer and does not discriminate on the basis of race, color, religion, ethnic or national origin, sex, disability, age (40 and over), status as a protected veteran, genetic information or any other category protected by federal or state law. Inquiries regarding the nondiscrimination policies should be directed to equity@tntech.edu.CHONGQING UNIVERSITY, School of Economics and Business Administration, founded in 1937, is one of the best business schools in West China and was accredited by AACSB and AMBA. Qualifications: Applicants must have gotten a Ph.D. degree within three years and have an established record of excellence in scholarly research with great potential. Type 1: Doctoral degree holders who graduated from top 100 overseas universities (current year's ranking of ARWU, QS, THE and USNEWS). Type 2: Doctoral degree holders who graduated from world-renowned universities. Compensation: Type 1: RMB 370,000–400,000 yuan/year plus research reward. Type 2: RMB 270,000–300,000 yuan/year plus research reward. After the 3+ years performance evaluation, candidates who meet relevant requirements can apply for tenured faculty positions. Contact: Ms. Li, Ms. Hu, School of Economics and Business Administration, Chongqing University, #174 Shazhengjie Street, Shapingba District, Chongqing, 400044, China; Phone: 86-23-65112654, Email: sebarcyj@cqu.edu.cn.UNIVERSITY OF NEBRASKA AT KEARNEY, Department of Accounting, Finance, and Economics invites applications for a position in accounting at the rank of Assistant Professor to begin in Fall 2021. While open to all areas, preference will be given to the areas of tax and cost/managerial. Responsibilities: Teaching undergraduate and graduate accounting courses; conducting scholarly research that leads to publication in quality peer-reviewed journals; participation in internal and external service activities; advising and interacting with students; and pursuing professional development. Required Qualifications: A Ph.D. in accounting, or D.B.A. in accounting (ABD within one year of completion is acceptable); degree must be from an AACSB-accredited institution; ability to provide high-quality teaching; ability to conduct high-quality research; and excellent oral and written communication and interpersonal skills. Preferred Qualifications: Professional certification (CPA, CMA); professional work experience; university teaching experience; and quality publication history. See: https://www.unk.edu/offices/human_resources/employment_opportunities.phpRICE UNIVERSITY, Jones Graduate School of Business invites applications for a tenure-track position in accounting. The appointment will be made at the rank of Assistant Professor beginning July 1, 2021. The successful candidate is expected to produce high-quality research in accounting that results in publications in top journals in the field and to effectively teach M.B.A. and Ph.D. courses in accounting (and/or related fields). More experienced senior candidates may be considered at higher ranks. If you wish to be considered by the search committee, upload materials at the link below indicating in your cover letter your appropriate rank. Applicants must complete all the requirements for a Ph.D. in accounting/related field by July 1st of the year employment commences. The application deadline is December 1, 2020, but applications will be accepted until the search is closed. Applicants should apply at: https://jobs.rice.edu/postings/23940/. Applications must include a cover letter, a curriculum vitae, research statement, teaching statement, copies of any teaching evaluations, job market paper, or any other research studies, and three letters of recommendation (applicants must provide information for three references who will be automatically contacted for letters of recommendation). Rice University is an Equal Opportunity/Affirmative Action Employer and actively encourages applications from women and underrepresented groups.NAVAL POSTGRADUATE SCHOOL, Graduate School of Defense Management, Monterey, CA invites applications for open rank, tenure-track positions in financial management. Candidates must qualify to join the faculty as active teachers and scholars. They should possess a terminal degree, such as a Ph.D., or its equivalent, in a relevant discipline, including (but not limited to) accounting, business administration, economics, public administration, or public policy. We are particularly interested in scholars with strong theoretical, methodological, and applied interests in financial management. The successful applicant must be able to teach core courses in budgeting, accounting, and/or managerial finance within the graduate program, in addition to one or more other courses within the financial management curriculum. Preference will be given to those candidates who can teach auditing and/or managerial accounting in private-sector and/or federal sector. Please see details at: https://nps.edu/web/gsdm/employment-opportunitiesSIENA COLLEGE, Department of Accounting and Business Law is seeking to hire a colleague with a particular interest and strength in Accounting Information Systems for Assistant/Associate Professor of Accounting tenure-track position. Review of credentials will start immediately. Preferred start date is September 2021. The ideal candidate will have demonstrated teaching excellence and an earned doctorate in accounting (or ABD). Significant professional experience and certification are desirable. S/he will also demonstrate the ability to maintain their academic qualifications under AACSB accreditation standards for both undergraduate and graduate teaching. A background screening will be required. Please submit cover letter, cv, teaching philosophy, research statements, teaching evaluations, and contact information for three references at: https://siena.interviewexchange.com/jobofferdetails.jsp?JOBID=123365/. Siena College is an Equal Opportunity Employer and all qualified applicants will receive consideration for employment without regard to race, color, religion, sex, sexual orientation or gender identity, national origin, disability status, protected veteran status, or any other characteristic protected by law.CHINA EUROPE INTERNATIONAL BUSINESS SCHOOL (CEIBS) invites applications for two open-rank faculty positions in financial accounting. Successful applicants are expected to teach related courses to M.B.A. and E.M.B.A. students and executive education program participants. The organizational language at CEIBS is English and faculty are based in Shanghai, Beijing, or Shenzhen (China). Applicants must have a Ph.D. (or equivalent) in accounting and a strong commitment to excellence in scholarly research and teaching. Associate and Full Professor applicants should have a proven track record of exceptional scholarship in accounting. Preference will be given to those who have relevant teaching experience, especially with Executive and M.B.A. students. Salary is competitive with top U.S. business schools and commensurate with qualifications. In addition, the school offers many generous benefits, including housing and child education allowances, medical insurance, and a pension plan. Moreover, to support excellence in research, the school offers generous research funding, teaching load reductions or bonuses for high-caliber scholarly publications, and a reduced teaching load for the first three years. Applicants should submit a curriculum vitae, course evaluations from prior teaching, recent samples of scholarly work, and the names of three scholars willing to evaluate the applicant's research and teaching ability. Please submit this information to: Ms. Daisy Li, Dean's Office at: ldaisy@ceibs.edu. Applications will be reviewed until positions are filled and will be kept confidential. CEIBS, a non-profit joint venture established in 1994 by the Chinese Government and the European Union, is the leading China-based international business school with M.B.A. (ranked No. 5 worldwide by Financial Times in 2020), E.M.B.A., Global E.M.B.A. (ranked No. 5 worldwide by Financial Times in 2019), Finance M.B.A., and Executive Education programs. CEIBS has campuses in Shanghai, Beijing, Shenzhen, Accra (Ghana), and Zurich (Switzerland). CEIBS is committed to teaching and research excellence and to educating responsible leaders versed in “China Depth, Global Breadth.”SANTA CLARA UNIVERSITY, Department of Accounting invites applications for a tenure-track position beginning Fall 2021. The position is for the rank of Assistant Professor, although established candidates with exceptional scholarly achievement may be considered for higher ranks. We encourage applications from candidates in all areas of research and teaching interests, especially those with an interest in teaching auditing. Candidates should have completed or nearly completed their Ph.D. and must demonstrate capacity to undertake scholarly research publishable in leading journals and to provide quality teaching. Applications must be submitted using the university's online application process at: https://www.scu.edu/hr/careers/employment-opportunities/faculty-job-postings/. Please submit a cover letter, cv, sample of research, evidence of teaching effectiveness, and three letters of recommendation. Applications will be accepted and reviewed until the position is filled. SCU is a private Jesuit university located in Silicon Valley. We provide housing subsidies and competitive summer research support. SCU is EEO/AA.PALM BEACH ATLANTIC UNIVERSITY, Rinker School of Business seeks an Assistant/Associate Professor of Accounting. Applicants are required to hold a doctoral degree in business with a major in accounting, preferably from an AACSB-accredited business school. Candidates must have: 18 graduate credit hours in accounting (those applicants not currently holding a terminal degree must have clear evidence of an expected completion of the doctoral degree prior to the start date); ability to be classified as a Scholarly Academic (SA) faculty member for AACSB purposes; the ability and interest in teaching in our graduate, evening, and online Master of Accountancy Program; evidence of a planned scholarly agenda consistent with expectations of a teaching, informed by scholarship-focused program; and a Christian commitment and the ability to integrate Christian faith into traditional coursework. Please provide evidence of quality teaching (teaching evaluations, syllabi, etc.) in your application letter, at: https://www.pba.edu/human-resources/faculty-admin-positions.html. Please also comment on inclusion of technology in accounting courses taught to date. The successful appointment is expected to have a strong commitment to teaching excellence and service to the School, the University, and the community.HUNAN UNIVERSITY, Business School of Business Administration was ranked as one of the top 12 in China and the top 1 in central China according to the Ministry of Education ranking published in 2012. The 2020 Global Ranking of Academic Subjects (Business Administration) flags it as No. 9 among universities in mainland China. Available Positions: Assistant Professor/Associated Professor/Full Professor in Finance, Econometrics, Organizational Behavior, Strategy, Innovation, Operations Management, Marketing, and Accounting. Number of vacancies: 5. Contract Duration: Five years. Requirements: Obtained a Ph.D. degree from an internationally renowned university. Research experience with outstanding academic achievements is a plus. Responsibilities: 1. Conduct full-time lecturing and research in the disciplines of management science and business administration; 2. Build research teams; advise young researchers for international competence; 3. Promote international influence of relevant disciplines; participate in curriculum construction and development; develop and coordinate international academic exchange events and collaboration; 4. Apply for research grants for national research projects; 5. Publish papers in international journals as the first or corresponding author affiliated to the Business School of Hunan University; and 6. Advise students on their course work, research and thesis.NAZARBAYEV UNIVERSITY, Graduate School of Business (NUGSB)—a small, but growing research-oriented faculty and in strategic partnership with Duke University's Fuqua School of Business—invites applications for faculty positions (all ranks) in the area of Accounting. Candidates should have a Ph.D. degree in the relevant field from an accredited institution. Located in Nur-Sultan, Kazakhstan, NUGSB is a new Western-style, English-language research-oriented business school and offers its faculty generous research time, efficient teaching load, and competitive salary. To support research activities and expand professional networks, NUGSB faculty spend time at Duke's Fuqua School of Business. For additional questions: Doron Israeli, doron.israeli@nu.edu.kz. Required application materials include: cover letter, curriculum vitae, copy of a research paper, and letters of recommendation. Please submit your application at: https://gsb.nu.edu.kz/working-at-nugsb/faculty/.CALIFORNIA STATE UNIVERSITY, LONG BEACH is looking for candidates for a tenure-track position with the following duties: Teach undergraduate and graduate Accounting courses, such as Financial Accounting, Managerial Accounting, Intermediate Financial Accounting, Cost Accounting, and Advanced Accounting (mode of instruction may include in-person, hybrid, online, and/or any combination thereof); engage in research, scholarly, and creative activities leading to presentation and publication; and participate in service to the Department, College, University, and community. Required Qualifications: Ph.D. or D.B.A. with a major in Accounting from AACSB-accredited business school. Degree at time of application or official notification of completion of the doctoral degree by August 1, 2021; demonstrated ability for effective teaching of Financial and Managerial Accounting courses at both the undergraduate and graduate levels; potential for scholarship leading to high-quality academic publications; potential for curriculum development; potential for service contributions to the Department, College, University and community; and commitment to working successfully with a diverse student population especially teaching and mentoring students from under-represented groups. Go to: https://www.csulb.edu/academic-affairs/faculty-affairs/assistant-professor-of-accountancy-2630DRAKE UNIVERSITY, College of Business and Public Administration (CBPA), School of Accounting, invites applications for a full-time, tenure-track Assistant/Associate Professor of Accounting for Fall 2021, teaching courses in Accounting at the undergraduate and graduate levels. Experience in financial reporting preferred. Normal teaching load is nine credits per semester. A doctorate in Accounting is preferred. ABD candidates close to completion will be considered. Salary is competitive with peer AACSB institutions. Drake University is a private, comprehensive university dedicated to quality teaching. It is located in Des Moines, Iowa, with a metropolitan population over 500,000. Enrollment is selective and limited to approximately 5,500 students in the schools and colleges of the University. The CBPA is accredited by AACSB. To apply, submit (1) a cover letter, (2) a current resume or curriculum vitae, (3) statement of teaching and research philosophy, (4) a diversity statement, and (5) names and contact information for three references to: https://drake.hiretouch.com/. Drake University is an Equal Opportunity Employer.NOVA SOUTHEASTERN, Accounting & Taxation Department has a Visiting Faculty position available starting January 2021 through May 2021 to teach undergraduate and graduate courses (onsite and online). Preference will be given to candidates teaching courses in cost/managerial accounting, accounting information systems, or auditing. Qualifications: Ph.D., D.B.A., or ABD in Accounting, or related field. Applications must be submitted online at: https://nsucareers.nova.edu/en-us/listing/, position #997994. Please submit a cover letter addressing your qualifications and teaching interests, curriculum vita, evidence of teaching excellence, unofficial transcript, and a list of three or more references. Please contact the Chair of the Accounting & Taxation Department, Dr. Joung Kim, joung@nova.edu, for any questions. Nova Southeastern is an Equal Opportunity Employer.CHRISTOPHER NEWPORT UNIVERSITY, Joseph W. Luter, III School of Business invites applications for a tenure-track position in Accounting, effective August 2021. Teaching assignments for this position will be a combination of international accounting, accounting systems, and/or auditing, in the undergraduate business program and courses in financial statement analysis and data analytics in the new Master of Financial Analysis (M.Fin.A.) program. The nominal teaching load for tenure track appointments is 3-3. Preference will be given to candidates with experience and knowledge in auditing and/or data analytics and those holding professional designations (CPA, CISA, CFE) or having had experience with a national accounting firm. A Ph.D. in Accounting or a related field is required for appointment at the rank of Assistant Professor. In some cases, exceptionally well-qualified candidates may be considered for appointment at a higher rank. ABD candidates who will not hold the Ph.D. by the time of appointment may be considered for appointment at the rank of Instructor. For more information, or to apply for this position, please visit: https://jobs.cnu.edu/postings/9821. Christopher Newport University, an Equal Opportunity Employer, is fully committed to Access and Opportunity.CALIFORNIA STATE UNIVERSITY, EAST invites applications for Assistant or Associate Professor position in accounting to begin Fall 2021. The are to teach undergraduate and/or graduate accounting, accounting auditing or courses, conduct academic research in areas of accounting, and provide service to the University. A candidate should (1) have an earned Ph.D. in Accounting or related field from an AACSB-accredited later the effective date of the appointment with in one or more of the following accounting, auditing, and or in Taxation or and in Accounting with professional tax experience; (2) demonstrate a record of scholarly (3) meet College of Business and Economics AACSB faculty standards for Scholarly (4) possess strong communication and (5) demonstrate experience in teaching, research, or service that has to to our commitment to diversity and Professional (CPA, or and work experience in accounting, auditing or are desirable. Review of applications will begin September 2020 and will until the position is filled. Please submit a letter of a complete and current contact information of three graduate a diversity statement, a teaching statement, copies of teaching evaluation, copies of major publications, and three letters of recommendation to the For your to STATE UNIVERSITY, The Jones College of Department of Accounting invites applications for the Chair of in Accounting. will include: teaching in an area of that to the of the program at both the graduate and undergraduate levels; for and executive education and that to our and other external the Department and the that will and in support of the with the Department, College, and University; and with external and and with the business and professional Requirements: A degree in Accounting, or a related field with professional experience in and in the of accounting. Applicants must have a of years of professional experience with and/or academic experience in accounting. Applicants must have and/or other professional such as related to the accounting Go to: OF AT College of Business Administration, Department of Accounting and Information Systems invites applications from qualified candidates for two tenure-track faculty positions in Accounting. areas of will be accepted although preference will be given to those with teaching in auditing, and financial accounting. Salary and are and commensurate with experience and qualifications. include scholarly research in top academic teaching at both undergraduate and graduate and of a Ph.D. degree in accounting from an AACSB-accredited by the starting date is with evidence of potential publication in top journals and quality interpersonal and communication are The expected starting date is September 1, 2021. are subject to Review of applications will begin and until the positions are filled. Applicants are to apply by 2020. To apply, please